Mikroenkapsulasi minuman herbal pokak madura menggunakan spray dryer sebagai imunomodulator - Siti Alfiatul Amani; Dodyk Pranowo; Susinggih Wijana (AGROINTEK, 2024)
Pokak is a variant of the Madurese ginger drink made from spices. The main ingredient is ginger, while other additional ingredients are cloves, cinnamon, nutmeg, and masohi/masoyi wood. In general, these drinks are sold in liquid form. The maceration method was used to obtain pokak extract while spray dryer was used to obtain Pokak powder. Pokak is believed to boost immunity, increase stamina and warm the body. The development of Pokak Madura in powder form can increase the sale value, be more practical in the making and have a longer shelf life. This study aims to determine the optimal composition and conditions of Pokak microencapsulation. The parameters used are maltodextrin concentration (4.05; 5; 10; 15; 15.94%) and inlet temperature (120.27; 125; 150; 175; 179.7 oC). The optimization method used to get the best pokak powder was RSM (Response Surface Methodology). Tests at this stage were the total flavonoid test, antioxidant test, and morphology or best pokak powder profile using SEM (Scanning Electron Microscopy). Optimization results for the best treatment were a maltodextrin concentration of 10.639% and an inlet temperature of 148.042 oC resulting in a total of 6.447 mg QE/gram flavonoids and a percentage of antioxidants of 13.078%. The morphology of the particles is wrinkled with an average particle size of 5.372 µm. Thus maltodextrin as a coating or coating material with DE 10-12 cannot form spherical-shaped powder particles.